The Incremental Added Value of Including the Head in 18F-FDG PET/CT Imaging for Cancer Patients - Abdelmalik, Amir G.; Alenzi, Saud; Muzaffar, Razi; Osman, Medhat M. (Frontiers in Oncology, 2013)
Purpose: To assess the value of extending the routinely used base-of-skull (BOS) to upper-thigh field of view (FOV) to include the head on 18F-FDG PET/CT in cancer patients. Methods: We retrospectively reviewed 1000 consecutive top-of-head to foot PET/CT studies. Abnormalities above BOS were categorized as unsuspected or known and were correlated with pathology, MRI/CT, and clinical follow-up. Results: Of the 1000 patients, 102 (10.2%) had potentially significant findings above BOS. Of these, 70/102 (69%) were known and 32/102 (31%) were unsuspected. Of the patients with unsuspected findings, follow-up data was unavailable in 7/32 (22%) and abnormalities were confirmed in 25/32 (78%). Of the 25 confirmed unsuspected findings, 4/25 (16%) were false positives and 21/25 (84%) were true positives. Of these, 13/21 (62%) were confirmed metastatic, and 8/21 (38%) were benign. Unsuspected finding of brain metastasis changed the management in 11/13 (85%) and staging in 4/13 (31%). Conclusion: Including the head in PET/CT FOV incidentally detected clinically significant findings in 2.1% (21/1000) of patients. The detection of previously unsuspected metastasis had significant impact on patient management and provided more accurate staging.